Efektivitas Online-based Group Stress Management Intervention terhadap Stres Remaja Perempuan Selama Pembelajaran Jarak Jauh - Sharfina Divo; Mita Aswanti Tjakrawiralaksana (Jurnal Ilmiah Psikologi MIND SET, 2023)
This study aimed to test the effectiveness of online-based group stress management intervention for adolescent girls experiencing increased stress due to the distance learning system implemented during the Covid-19 pandemic. The intervention program was conducted for 8 sessions with 8 participants aged 16-17, with each session lasting 60-90 minutes. The effectiveness of the intervention was measured using the Perceived Stress Scale (PSS) and Brief COPE questionnaire before, after, and one month after the intervention. The results showed a decrease in stress and an increase in effective coping strategies among the participants, indicating that online-based group stress management intervention can effectively address stress in adolescent girls during the implementation of distance learning systems due to the Covid-19 pandemic.